The Use of Science Comic Media on the YouTube Application to Cultivate Students' Interest in Learning at Elementary School 35 Bengkulu City - Hanifah, Aisyah Umu; Sari, Demi Lupita; Asvio, Nova; Wahyuni, Betti Dian; Friantary, Heny (International Journal on Advanced Science, Education, and Religion, 2025)
The purpose of this study is to describe the use of social studies comics on YouTube to foster student interest. The method used was descriptive qualitative, conducted at SDN 35, Bengkulu City, with data sourced from classroom teachers. The results indicate that the use of YouTube-based social studies comics in learning has been proven to increase student interest. This is evident in the learning process, which includes systematic and directed planning, implementation, and evaluation. During the planning stage, teachers developed learning materials in accordance with the Independent Curriculum and adapted the material to the characteristics and level of cognitive development of students. Selecting engaging and relevant media is a crucial factor in creating more meaningful learning. During the implementation stage, the use of social studies comic videos created a more interactive, enjoyable, and engaging learning environment, enabling students to become more active and enthusiastic in participating. Evaluation results also showed an increase in cognitive understanding and student interest compared to previous learning. Therefore, YouTube-based social studies comics can be used as an effective learning innovation to improve the quality of student learning processes and outcomes in elementary schools.